Chemical Hermaphroditism: The Potential of the Cr(CO)3 Moiety To Stabilize Transition States and Intermediates with Anionic, Cationic, or Radical Character at the Benzylic Position - Merlic, Craig A; Walsh, Joseph C; Tantillo, Dean J; Houk, K. N (Journal of the American Chemical Society, 1999)
It is known that both benzylic cations and anions are stabilized by Cr(CO)3 complexation. This unusual characteristic of chromium arenes has been the subject of many synthetic, spectroscopic, and physical organic studies over the last four decades. The effect of Cr(CO)3 on benzylic radicals has received comparatively little attention, however. In this report, cyclopropylcarbinyl anions, cations, and radicals substituted with both phenyl and Cr(CO)3-phenyl groups are shown to rearrange via ring-opening to produce, selectively, Cr(CO)3-stabilized benzylic anions, cations, and radicals, implying that the Cr(CO)3 moiety is capable of stabilizing transition states with ionic or radical character at the benzylic position. The highest selectivity (>99:<1) was observed in the anionic reaction, slightly lesser selectivity (95:5) was observed in the cationic reaction, and only modest selectivity (2.5:1) was observed in the radical reaction. A parallel trend in ground-state stabilities of Cr(CO)3-complexed benzyl anion, cation, and radical is predicted by density functional theory calculations. These calculations reveal that considerable structural distortions of both benzyl anion and cation occur upon complexation, but that little distortion occurs for benzyl radical. The connections between Cr(CO)3 complexation and the stability of the complexed species are explained in terms of interactions between frontier molecular orbitals of the Cr(CO)3 and benzyl fragments.